TLR7 mutations leading to enhanced TLR7 signaling in humans - Yanick J. Crow; Michael P. Gantier (Journal of Human Immunity, 2026)
Three studies in this issue of JHI (https://doi.org/10.70962/jhi.20250194, https://doi.org/10.70962/jhi.20250196, and https://doi.org/10.70962/jhi.20250199) extend our understanding of the genetic, molecular, and clinical characteristics of human disease associated with a gain of TLR7-mediated signaling.